Pengaturan Pemenuhan Hak Pelayanan Publik Oleh Pemerintah Daerah (LEGAL DIALOGICA, 2025)
This research aims to find out the regulation of the fulfilment of public service rights by the regional government of Pangkajene and Islands Regency and to find out the factors that influence the fulfilment of public service rights by the regional government in Pangkajene and Islands Regency. This study uses a normative-empirical legal research method, which combines two types of research. Normative legal research is used to obtain secondary data. Empirical legal research is a legal research method used to examine the law in a practical sense and to study how the law works in a particular community. The results of this study indicate that the role of the local government in regulating the fulfilment of public service rights in Pangkajene and Kepulauan Regency has sought to optimise the process of fulfilling public service rights by striving to the utmost to achieve the fulfilment of public service rights in accordance with its regulations and in line with existing norms or regulations in Indonesia. However, the local government of Pangkajene and Islands Regency has not been able to implement specific regulations to carry out the fulfilment of public services, especially in the island areas that are far from the mainland of Pangkajene and Islands Regency. The factors influencing the fulfilment of public service rights in accordance with the regulations of Law Number 25 of 2009 on public services are as follows. Additionally, the low level of public awareness regarding their rights and obligations under the regulations also affects the provision of public services in Pangkajene and Islands Regency. This research recommendation serves as an important note in the implementation of regulations for the provision of public services by the local government in accordance with the applicable regulations, aiming to establish appropriate and effective regulations.Abstrak:Penelitian Ini bertujuan untuk mengetahui pengaturan pemenuhan hak pelayanan publik oleh pemerintah daerah Kabupaten Pangkajene dan Kepulauan dan untuk mengetahui faktor-faktor yng mempengaruhi pemenuhan hak pelayanan publik oleh pemerintah daerah di Kabupaten Pangkajene dan Kepulauan. Penelitian ini menggunakan metode penelitian hukum normatif-empiris atau jenis penelitian yang menggabungkan dua jenis penelitian sekaligus. penelitian hukum normatif yang berfungsi untuk memperoleh data sekunder. Penelitian hukum empiris yaitu suatu metode penelitian hukum yang berfungsi untuk melihat hukum dalam artian nyata serta meneliti bagaimana cara hukum bekerja di suatu lingkungan masyarakat. Hasil penelitian ini menunjukkan bahwa peranan pemerintah daerah terhadap pengaturan pemenuhan hak pelayanan publik di Kabupaten Pangkajene dan Kepulauan telah berusaha mengoptimalkan proses pemenuhan hak pelayanan publik dengan berupaya semaksimal mungkin mewujudkan tercapainya pemenuhan hak pelayanan publik sesuai dengan pengaturanya dan sejalan dengan norma atau pengaturan yang ada di Indonesia. Akan tetapi, pemerintah daerah Kabupaten Pangkajene dan Kepulauan belum bisa melaksanakan pengaturan khusus untuk melaksanakan pemenuhan pelayanan publiknya  terutama di daerah-daerah kepulauannya yang terpisah jauh dari daratan utama Kabupaten Pangkajene dan Kepulauan. Adapun, yang menjadi faktor-faktor yang mempengaruhi pemenuhan hak pelayanan publik yang sesuai dengan pengaturan Undang-Undang Nomor 25 Tahun 2009 tentang pelayanan publik. Selain itu, rendahnya kesadaran masyarakat akan hak dan kewajibannya terhadap pengaturan juga memengaruhi pemenuhan pelayanan publik  di Kabupaten Pangkajene dan Kepulauan. Rekomendasi Penelitian ini sebagai suatu catatan penting dalam pelaksanaan penerapan pengaturan pemenuhan pelayanan publik oleh pemerintah daerah sesuai dengan pengaturannya yang berlaku demi terciptanya pengaturan yang sesuai dan terlaksana.